Camping de Lujo y la Incidencia en el Flujo Turístico de la Finca la Clarita, parroquia de Papallacta, provincia de Napo - María José, Granda Muñoz (2021)
ABSTRACT The new tourism trends with innovative characteristics that allow dynamizing the economies have triggered a low tourist flow in Finca La Clarita, Papallacta parish, Napo province, which hinders the generation of economic income for tourism. This research aims to determine the incidence of luxury camping and the tourist flow of Finca La Clarita. The methodology includes the treatment of descriptive and quantitative methods. A total of 246 surveys were applied, which made it possible to test the alternative hypotheses and know tourists' perception regarding the two variables under study, luxury camping, and tourist flow. Thus, 92.2% would like to see domes built for luxury camping, 78.9% would like to visit the domes with their pets, 54.1% would like to have door-to-door transportation to reach the luxury domes, 86.2% would agree to develop nature activities, and 73.6% said they would require food service. Likewise, the dependent variable, tourist flow, was characterized by the following data. 93.5% strongly agree with traveling an hour from Quito's city to get to the domes. 93.1% think that luxury camping would improve the tourist image of the parish. It is concluded that luxury camping impacts the influx of tourists. Therefore, it is recommended to develop an alternative tourism project with a market, technical, administrative, legal, and economic-financial study. Keywords: Luxury camping, tourist flow, tourism, lodging, domes. Reviewed by: Ms.C. Ana Maldonado León ENGLISH PROFESSOR C.I.0601975980